Varying responses of field-selected herbicide-resistant rigid ryegrass (Lolium rigidum) populations to combinations of phorate with PPI herbicides. Issue 4 (13th July 2020) - Brunton, David J.; Boutsalis, Peter; Gill, Gurjeet; Preston, Christopher
Abstract: Organophosphate insecticides, which have the capacity to inhibit specific herbicide-degrading (cytochrome P450) enzymes, have been used to explore metabolic herbicide-resistance mechanisms in weeds. This study investigates the response of seven field-selected rigid ryegrass ( Lolium rigidum Gaudin) populations to herbicides from three different sites of action in the presence or absence of the P450 inhibitor phorate. Phorate antagonized the thiocarbamate herbicides triallate and prosulfocarb (8-fold increase in LD50 ) in multiple resistant L. rigidum populations with resistance to three different site-of-action herbicides. In contrast, phorate synergized trifluralin and propyzamide in some populations, reducing the LD50 by 50%. Conversely, treatment with phorate had no significant effect on the LD50 for S -metolachlor or pyroxasulfone (inhibitors of very-long-chain fatty-acid synthesis). Phorate has diverse effects that are herbicide and population dependant in field-selected L. rigidum, suggesting P450 involvement in the metabolism of trifluralin and failure to activate thiocarbamate herbicides in these populations. This research highlights the need for implementation of diverse approaches other than herbicide alone as part of a long-term integrated strategy to reduce the likelihood of metabolism-based resistance to PPI herbicides in L. rigidum .